A PARTNERSHIP OF THE POLICE AND SOCIETY TO COMBAT RELIGIOUS RADICALISM (DIGNIFIED JUSTICE PHILOSOPHY ) - Christina Maya Indah; Teguh Prasetyo; Jeferson Kameo (Surakarta Law and Society Journal, 2019)
Modern civilization dictates that the police have to adapt to a frame work of a modern police. In this research we argued that the Police should change from the traditional policing to a Dignified Justice Policing. In this perspective, based on the findings in the spirit of the people manifested throughout the existing rules and regulations relating to the community policing (CP) the police must always be able to develop the social defence system. In this scheme, the policy is obliged to serve and to protect the society; and in particular to create a concept of justice, in which human should be treated humane. In the modern concept of policing, the Police must have a close and built a strong cooperation or partnership with society. With a close and strong partnership with the society, the modern police would be able to overcome the threat of any criminalities, particularly the religious radicalism and extremism in its society. This is particularly relevant in the rescent times where religious radicalism is a concern within any societies. Efforts to find a strategy to pursue such an aim has been drawn to a new construction or legal ideas which in this work has been coined as the Dignified Justice philosophy. This paper will describe and analise the findings with the utilization of the Dignified Justice philosophy as an alternative policy to justify a close and strong cooperation between the police and society in an effort to combat or overcome criminalities in the society and simultaneously protect the society from dangerous elements in it. One of the concern that has drawn serious attention is the phenomenon of religious extremism in the community. Key words : Police, Society, Religous Radicalism.